Motor subtypes and clinical characteristics in sporadic and genetic Parkinson's disease groups: analysis of the PPMI cohort - Jeong, Eun Hye; Lee, Jae Yong; Han, Sun-Ku; Song, Yoo Sung (Frontiers in Neurology, 2023)
Introduction The extensive clinical variations observed in Parkinson's disease (PD) pose challenges in early diagnosis and treatment initiation. However, genetic research in PD has significantly transformed the clinical approach to its treatment. Moreover, researchers have adopted a subtyping strategy based on homogeneous clinical symptoms to improve clinical diagnosis and treatment approaches. We conducted a study to explore clinical characteristics in genetic PD groups with motor symptom subtyping. Methods Data was driven from the Parkinson's Progression Markers Initiative (PPMI) database. The sporadic PD (sPD) group and the genetic PD group including patients with leucine-rich kinase 2 (LRRK2) or glucosylceramidase β (GBA) mutations were analyzed. Motor subtyping was performed using Movement Disorder Society-Unified Parkinson's disease rating scale (MDS-UPDRS) scores. I-123 FP-CIT SPECT scans were used to calculate specific binding ratios (SBRs) in the caudate and putamen. Clinical symptoms of each group were also compared. Results MDS-UPDRS III scores were lower in the LRRK2 group, compared with the GBA and sPD group (P < 0.001), but no significant differences in striatal SBRs. The putaminal SBR value of the LRRK2 group was higher than the sPD group (P < 0.05). Within the GBA group, we observed lower SBR values in the postural instability/gait difficulty (PIGD) subtype GBA group compared to the tremor-dominant (TD) subtype GBA group (P < 0.05). The TD subtype GBA group exhibited superior putaminal SBRs compared to the TD subtype sPD group (P < 0.05). The TD subtype LRRK2 group had better putaminal SBR values (P < 0.001) and MDS-UPDRS Part III scores (P < 0.05) compared to the TD sPD group. Discussions Our subtyping approach offers valuable insights into the clinical characteristics and progression of different genetic PD subtypes. To further validate and expand these findings, future research with larger groups and long-term follow-up data is needed. The subtyping strategy based on motor symptoms holds promise in enhancing the diagnosis and treatment of genetic PD.